Soil Nematodes and Their Prokaryotic Prey Along an Elevation Gradient in The Mojave Desert (Death Valley National Park, California, USA) - Alyxandra Pikus; Megan Riley; Cecilia O’Leary; Jasmine Felder; Timothy McLlarky; Archana Narla; Brendan Kavanaugh; Kelsey Sutton; Amy Treonis; Sarah Thomas (Diversity, 2012)
We characterized soil communities in the Mojave Desert across an elevation gradient. Our goal was to test the hypothesis that as soil quality improved with increasing elevation (due to increased productivity), the diversity of soil prokaryotes and nematodes would also increase. Soil organic matter and soil moisture content increased with elevation as predicted. Soil salinity did not correlate to elevation, but was highest at a mid-gradient, alluvial site. Soil nematode density, community trophic structure, and diversity did not show patterns related to elevation. Similar results were obtained for diversity of bacteria and archaea. Relationships between soil properties, nematode communities, and prokaryotic diversity were site-specific. For example, at the lowest elevation site, nematode communities contained a high proportion of fungal-feeding species and diversity of bacteria was lowest. At a high-salinity site, nematode density was highest, and overall, nematode density showed an unexpected, positive correlation to salinity. At the highest elevation site, nematode density and species richness were attenuated, despite relatively high moisture and organic matter content for the soils. Our results support emerging evidence for the lack of a relationship between productivity and the diversity of soil nematodes and prokaryotes.